Motivation Behind the Preference of Distance Education of Higher Education Students - Pidbutska, N. V.; Knysh, A. Ye.; Chebakova, Yu. G.; Shtuchenko, I. Ye.; Babchuk, Olena (Foundation Pro Scientia Publica, Poland, 2022)
It was determined that 38% of students are positive about distance education and see great opportunities for its implementation. But only 22.75% of students consider distance learning to be the best option for educational process organisation, and 21.8% are in favour of an exclusive face-to-face format. The most popular form among students is a mixed form of education (55.45%). Students with a positive attitude to distance education are characterised by the highest scores on intrinsic motivation, self-efficacy and career motivation.
Keywords: distance education; online learning; science motivation; students; personality development